An approach to identifying, measuring, and generating reciprocal spillovers - Caicedo Asprilla, Henry (Cuadernos de Administración, 2012)
This paper reviews the literature on reciprocal spillovers to contribute to understanding these externalities in industrial organizations, location of multinational firms, and agglomeration of firms. Although the capture and representation of such externalities has been criticized, some work is presented herein showing the nature and importance of reciprocal spillovers. The method applied was bibliometric citation analysis using the Google Scholar database. Evidence exists that reciprocal spillovers manifest through patent citations, mobility of labor among firms, learning forms of organizations and production, magazine distribution channels, etc. It is, likewise, shown that reciprocal spillovers arise due to network configuration among multinational firms and the arrival of regional players. We conclude that while reciprocal spillovers are difficult to capture and measure, when the analysis is based on the technology transfer process, it is possible to trace these types of externalities.